Antidiabetic effect of kaempferol a flavonoid compound, on streptozotocin-induced diabetic rats with special reference to glycoprotein components - Chandramohan, Govindasamy; Al-Numair, Khalid S.; Alsaif, Mohammed A.; Veeramani, Chinnadurai (Progress in Nutrition, 2014)
Flavonoids have anti-inflammatory and antioxidative effects and thus may protect against diabetic complications. In our early study, kaempferol at an optimum dose of 100 mg was decreased plasma glucose level and increased the insulin levels and also kaempferol exhibited hypolipidemic action in streptozotocin-diabetic rats after 45 days of treatment. The aim of this study was planned to investigate the effect of kaempferol a flavonoid compound on plasma and tissues glycoprotein components in streptozotocin (STZ)-induced diabetic rats. Diabetes was induced into adult male albino rats of the Wistar strain, weighing 180–200 g, by intraperitoneal administration of streptozotocin (40 mg/kg of body weight (BW)). Kaempferol at a dose of 100 mg/kg BW was administered once daily for 45 days to normal and STZ-induced diabetic rats. The levels of plasma and tissues (liver, kidney and heart) glycoproteins containing hexoses, hexosamines and fucose were increased significantly in diabetic rats. In addition, the level of sialic acid significantly increased in plasma, liver and heart while decreased in kidney of STZ-induced diabetic rats. Treatment of kaempferol to diabetic rats, the above metabolic alteration of glycoprotein reverted towards normal level. These results indicate that kaempferol can potentially ameliorate glycoprotein abnormalities related to the risk of diabetes mellitus.